Promoting caste equality in the labor market: The role of self-confidence - Qiqi Wang; Tushi Baul; Sujoy Chakravarty; Tanya Rosenblat (PLoS ONE, 2025)
We study how people perceive the self-confidence of individuals from different castes in India. In an experimental Indian labor market where employers and workers belong to different castes, employers evaluate worker resumes to predict the future productivity of workers who perform a real effort task. The baseline group uses resumes that reveal a productivity signal i.e.- performance in a practice task and caste information, while the treatment group receives an additional measure of worker self-confidence. We find that employers in both groups exhibit a discriminatory wage differential against lower caste workers. However, employers in the treatment group weigh lower caste workers’ self-confidence more heavily than that of higher caste workers. This differential effect of confidence compensates for the lower evaluation and hence wage given to lower caste workers due to discrimination. From a policy perspective, these findings highlight the importance of non-cognitive skill training, such as training sessions for employment interviews where applicants can signal their self-confidence through interaction with employers.